2007
DOI: 10.1177/147323000703500208
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Analysis of PCNA, Ki67 and p53 in Nasal Polyposis and Sinonasal Inverted Papillomas

Abstract: Immunoreactivity of proliferating cell nuclear antigen (PCNA), Ki67 and p53 in inflammatory nasal polyp and inverted papilloma tissues was investigated. Immunohistochemistry was performed using a standard avidin-biotin-peroxidase method, and the immunoreactivity of PCNA, Ki67 and p53 was quantified by counting immunostained nuclei in at least 1000 epithelial cells. The mean labelling index (percentage of immunostained cells) for PCNA was 40.68 in the inverted papilloma group and 14.73 in the nasal polyp group,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 10 publications
(11 reference statements)
5
17
0
Order By: Relevance
“…This parameter was also significantly higher in sinonasal IP group in comparison with controls. Similarly to our study, other authors also demonstrated higher immunoexpression of Ki67 in squamous cell carcinoma and nasal IPs with dysplasia, suggesting that a high proliferative rate is a characteristic of IP-associated malignant diseases [43][44][45][46][47]. Kawasaki et al [47] postulated survivin as the strongest apoptosis inhibitory factor, involved in the regulation of cellular proliferation in colon cancer.…”
Section: Discussionsupporting
confidence: 64%
“…This parameter was also significantly higher in sinonasal IP group in comparison with controls. Similarly to our study, other authors also demonstrated higher immunoexpression of Ki67 in squamous cell carcinoma and nasal IPs with dysplasia, suggesting that a high proliferative rate is a characteristic of IP-associated malignant diseases [43][44][45][46][47]. Kawasaki et al [47] postulated survivin as the strongest apoptosis inhibitory factor, involved in the regulation of cellular proliferation in colon cancer.…”
Section: Discussionsupporting
confidence: 64%
“…Recently, it is also found the elevated PCNA in IP compared to the sinonasal polyps by Mumbuc et al [3]. The PCNA could interact with CDK1 and promote the cell entry to the cell cycle to the consequent proliferation and cancerization.…”
Section: Discussionmentioning
confidence: 90%
“…Epistaxis and nasal obstruction with facial pain or headache attacked when the nose or sinuses mucosa bear the IP [2]. Although the IP originating from the outlining respiratory membrane belongs to a benign epithelial neoplasm, the local invasiveness, higher recurrence rate, and malignant transformation make it difficult to treat [3]. The malignant transformation rate is 5–10% and many of them are synchronous presenting with squamous cell carcinoma [4].…”
Section: Introductionmentioning
confidence: 99%
“…Serum SCC antigen may be a useful biologic marker in patients with sinonasal IP [205207]. Proliferating cell nuclear antigen labeling index (PCNA-LI) can be used as a strong independent indicator to judge tumor aggressive behavior, proliferative activity, development of local or regional metastases, and prognosis in nasal inverted papilloma [208, 209]. …”
Section: Etiology and Pathogenesismentioning
confidence: 99%